Pembentukan Kawasan Ekonomi Khusus (KEK) di Perbatasan Wini, Indonesia dengan Oecusse, Timor Leste Guna Meningkatkan Kesejahteraan, Ketahanan Pangan dan Keamanan di Perbatasan - Agung Nugroho, Bonifasius; Maarif, Syamsul; Yulivan, Ivan; Prayitno, Arief (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The border area in Wini, Indonesia with Oecusse, Timor-Leste with its unique geographical and economic characteristics, requires better management in order to become a profitable economic and trade center zone while maintaining the stability of food availability and security. The establishment of a Special Economic Zone (SEZ) on the border of Wini, Indonesia with Oecusse, Timor Leste has great potential to improve the welfare of the people around the border, support food security and improve border security. This study aims to analyze the potential of SEZ development in Wini in strengthening food security through increased food availability and distribution, as well as supporting border security through more systematic and sustainable management of border resources. The establishment of an SEZ will allow the Wini border region to optimize its natural resources and enhance economic cooperation with Timor-Leste, as well as provide a solution to the challenges in border management that have often been a sensitive issue.